Synthesis of thiourea chitosan and thiourea chitosan metal complexes and antibactarial activity - Tan et al, Le Van (Vietnam Journal of Chemistry, 2014)
Chitosan and its derivatives are becoming increasingly important natural polymers because of their unique combination of properties like biodegradability, biocompatibility and bioactivity, in addition to attractive physical and mechanical properties. Here we wish to report the synthesis and characterization of thiourea chitosan and its metal-complex. Thiourea chitosan was prepared by the reaction of chitosan with ammonium thiocyanate in ethanol. Its metal complex was prepared by dissolving thiourea chitosan in 1% CH3COOH solution follow by adding metal salt solution.  Antimicrobial activities of the complexs were evaluated against three species of bacteria. These complexs had an effect on study bacteria, which minimum inhibition concentrate (MIC) values against bacteria were 2 times lower than those of Thiourea-chitosan; the complex had higher antibacterial activity on Staphylococcus aureus than E. coli and Pseudomonas aeruginosa.